The Australian Child Maltreatment Study (ACMS): protocol for a national survey of the prevalence of child abuse and neglect, associated mental disorders and physical health problems, and burden of disease. Issue 5 (11th May 2021) - Mathews, Ben; Pacella, Rosana; Dunne, Michael; Scott, James; Finkelhor, David; Meinck, Franziska; Higgins, Daryl J; Erskine, Holly; Thomas, Hannah J; Haslam, Divna; Tran, Nam; Le, Ha; et al.
Abstract : Introduction: Child maltreatment (physical abuse, sexual abuse, emotional abuse, neglect and exposure to domestic violence) is widely understood to be associated with multiple mental health disorders, physical health problems and health risk behaviours throughout life. However, Australia lacks fundamental evidence about the prevalence and characteristics of child maltreatment, its associations with mental disorders and physical health, and the associated burden of disease. These evidence gaps impede the development of public health strategies to better prevent and respond to child maltreatment. The aims of this research are to generate the first comprehensive population-based national data on the prevalence of child maltreatment in Australia, identify associations with mental disorders and physical health conditions and other adverse consequences, estimate attributable burden of disease and indicate targeted areas for future optimal public health prevention strategies. Methods and analysis: The Australian Child Maltreatment Study (ACMS) is a nationwide, cross-sectional study of Australia's population aged 16 years and over. A survey of approximately 10 000 Australians will capture retrospective self-reported data on the experience in childhood of all five types of maltreatment (physical abuse, sexual abuse, emotional abuse, neglect and exposure to domestic violence). A customised, multimodule survey instrument has been designed to obtain information including: the prevalence and characteristics of these experiences; diagnostic screening of common mental health disorders; physical health; health risk behaviours and health service utilisation. The survey will be administered in March–November 2021 to a random sample of the nationwide population, recruited through mobile phone numbers. Participants will be surveyed using computer-assisted telephone interviews, conducted by trained interviewers from the Social Research Centre, an agency with extensive experience in studies of health and adversity. Rigorous protocols protect the safety of both participants and interviewers, and comply with all ethical and legal requirements. Analysis will include descriptive statistics reporting the prevalence of individual and multitype child maltreatment, multiple logistic and linear regression analyses to determine associations with mental disorders and physical health problems. We will calculate the population attributable fractions of these putative outcomes to enable an estimation of the disease burden attributable to child maltreatment. Ethics and dissemination: The study has been approved by the Queensland University of Technology Human Research Ethics Committee (#1900000477, 16 August 2019). Results will be published to the scientific community in peer-reviewed journals, scientific meetings and through targeted networks. Findings and recommendations will be shared with government policymakers and community and organisational stakeholders through diverse engagement activities, a dedicated Advisory Board and a systematic knowledge translation strategy. Results will be communicated to the public through an organised media strategy and the ACMS website.